PERBEDAAN KADAR KOLESTEROL TOTAL DAN TRIGLISERIDA PADA ANAK SINDROM NEFROTIK RELAPS DAN REMISI DI RSUD ULIN BANJARMASIN - Siti Annisa Rezki; FX Hendriyono; Selli Muljanto (Homeostasis, 2019)
Abstract: Hyperlipidemia is one of an important characteristics of nephrotic syndrome (NS). This study aims to determine the differences between total cholesterol and triglyceride levels in childrens with relapse and remission NS in Ulin General Hospital Banjarmasin from January 2017 - August 2018. A total of 26 childrens with NS were selected by purposive sampling method according to inclusion criteria. Among these, 15 childrens were in relapse and 11 childrens were in remission. Hypercholesterolemia were found in 93% of childrens with relapse NS and in 27% of childrens with remission NS, while hypertriglyceride were found in 67% of childrens with relapse NS and in 36% of childrens with remission NS. The mean total cholesterol levels in childrens with relapse NS is 374±38 mg/dL, was higher than those in remission, which is 168±12 mg/dL. The mean triglyceride levels in childrens with relapse NS is 267±186 mg/dL, also higher than those in remission, which is 130±78 mg/dL. The results of the analysis using an unpaired T test with a confidence level of 95%. This study can concluded that there were significant differences between total cholesterol (p = 0,000) and triglyceride levels (p = 0,030) in children with relapse and remission NS. Keywords: relaps nephrotic syndrome, nephrotic syndrome, remission, total cholesterol, triglyceride Abstrak: Hiperlipidemia merupakan karakteristik penting pada sindrom nefrotik (SN). Penelitian ini bertujuan untuk mengetahui perbedaan kadar kolesterol total dan trigliserida pada anak SN relaps dan remisi di RSUD Ulin Banjarmasin periode Januari 2017 – Agustus 2018. Sebanyak 26 anak SN yang terbagi atas 15 SN relaps dan 11 SN remisi dipilih secara purposive sampling sesuai kriteria inklusi. Didapatkan kejadian hiperkolesterolemia sebanyak 93% pada SN relaps dan 27% pada SN remisi, sedangkan kejadian hipertrigliseridemia sebanyak 67% pada SN relaps dan 36% pada SN remisi. Rerata kadar kolesterol total dan trigliserida pada SN relaps lebih tinggi dari SN remisi. Rerata kadar kolesterol total pada SN relaps adalah 374±38 mg/dL dan SN remisi adalah 168±12 mg/dL. Rerata kadar trigliserida pada SN relaps adalah 267±186 mg/dL dan SN remisi adalah 130±78 mg/dL. Hasil analisis menggunakan uji T tidak berpasangan dengan tingkat kepercayaan 95%. Berdasarkan penelitian yang dilakukan dapat diambil kesimpulan bahwa terdapat perbedaan bermakna antara kadar kolesterol total (p=0,000) dan trigliserida (p=0,030) pada anak SN relaps dan remisi. Kata-kata kunci: sindrom nefrotik relaps, sindrom nefrotik, remisi, kolesterol total, trigliserida